Rhodium-Catalyzed Dehydrogenative Borylation of Cyclic Alkenes - Kondoh, Azusa (2010)
A rhodium-catalyzed dehydrogenative borylation of cyclic alkenes is described. This reaction provides direct access to cyclic 1-alkenylboronic acid pinacol esters, useful intermediates in organic synthesis. Suzuki-Miyaura cross-coupling applications are also presented.